The Role of Internal Audit Function in the Performance of Rwanda Mutual Health Insurance Fund. Case of Gicumbi District - Bizimungu, Jean (Kabale University, 2023)
This study was carried out on the role of the internal audit function in the performance of the Anda Mutual Health Insurance Fund in the case of Gicumbi District. The study sought to examine and assess the impact of the internal audit function on the performance of the Anda.Health Insurance Fund in Rwanda It was also to highlight the role played by internal auditing in achieving the goals of the Mutual Health Insurance Fund of the Gicumbi District and to verify the internal controls used by MHIF in implementing the Mutual Health Insurance Fund in the Gicumbi District. The Mutual Health Insurance Fund of Gicurnbi District has caught the attention of the internal audit system is an effective tool for performance amelioration and is considered a victory to escape mismanagement. In the Rwandan context, this same initiative and hope have been emphasized in the country's mismanagement reduction strategy papers. The study took the case of Gicumbi District, which was one of 30 districts in Kwanda. To achieve the study's objectives, 50 MHIF staff members from two branches in the Gicumbi District were interviewed.Semi-structured questionnaires were used to collect primary data, books from libraries, and other documents. used to collect secondary data. It has been found that the Internal Audit Unit can assist the MHIF in maintaining its profitability without compromising its sustainability. As a result, the study recommended that, in order to achieve quality performance from MHIFs in Rwanda, the government, MHIF administrators, and other stakeholder groups ensure effective internal control. The conclusion was that the internal audit function is a necessary requirement, and suggestions were made that the Rwandan government enhance this service to cover the performance of mutual health insurance funds.